Deflation : current and historical perspectives - Burdekin, Richard C. K. (Richard Charles Keighley), 1958-; Siklos, Pierre L., 1955- (Cambridge, UK ; New York : Cambridge University Press, 2004)
This text explores some of the key themes of deflation, examining links between monetary policy, goods price movements and asset price movements.
Includes bibliographical references (p. 331-351) and index.
oif 01/09/15
Loan
Keywords: Deflation (Finance); Monetary policy; Prices